An assembling algorithm for fixture in an assembly process planning system. (June 2020) - Liu, Xiaojun; Xu, Xiaokang; Yi, Yang; Ni, Zhonghua; Zhang, Yang
Three-dimensional assembly process planning is a precondition for achieving full product lifecycle management based on three-dimensional modelling. Information expression and management operations of fixture models are key to three-dimensional assembly process planning systems. To reasonably and efficiently achieve the goal of planning assembly processes with a fixture model, the application of a fixture information model to a three-dimensional assembly process planning system is investigated. First, to manage tooling information, a fixture information model is defined that consists of management information, display information, geometric information, assembly constraints and degrees of freedom. Then, based on the analysis of the degrees of freedom of components and the assembly constraint relationship, a method of solving assembly constraints based on degrees of freedom reasoning is proposed. Finally, by using the method of solving assembly positioning based on geometric constraints, the pose transformation and assembly positioning of parts are achieved. Through the development of a tooling function module, the three-dimensional assembly process planning system is improved. The feasibility of the above method is verified using part of a spacecraft as an example.